Mathematical model of two parallel synchronous motors supplied from current type frequency converter - Sergelen, Byambaa; Pavelka, Jiří; Tušla, Petr (Communications - Scientific letters of the University of Zilina, 1999)
The contribution describes the mathematical model of electrical drive composed of two parallel synchronous motors. Besides the equations there is mentioned block scheme in MATLAB and simulation results of the starting of two synchronous motors supplied from network. The next stage of research work will be to create the mathematical model of synchronous motors supplied from one current type frequency converter.